”MATA KETIGA”: SÈ LAÈN, SANG PEMBEBAS SISTEM PENDIDIKAN TINGGI AKUNTANSI - Iwan Triyuwono (Universitas Brawijaya, 2010)
The objectives of the study are to criticize the existing accounting education especially in Indonesian universities and to give an alternative idea for a better one. It is done as there is a strong indication that accounting education is driven by intellectual intelligence, market, and other artificial interests. Through a deconstruction approach and critical analysis, the study suggests the internalization of “Mata Ketiga” (the Third Eye) in accounting curriculum. Mata Ketiga, that refers to spiritual intelligence, is “the Other” that is consciously entered to the singularity of intellectual intelligence of modern curriculum. Under the internalization of Mata Ketiga, accounting education can be emancipated from the domination of intellectual intelligence, market, and other artificial interests. By doing so, the education may guide an accounting student to find his/her “real self” without neglecting contemporary accounting competence.